Cathepsin L3 From Fasciola hepatica Induces NLRP3 Inflammasome Alternative Activation in Murine Dendritic Cells - Celias, Daiana Pamela; Corvo, Ileana; Silvane, Leonardo; Tort, José Francisco; Chiapello, Laura Silvina; Fresno, Manuel; Arranz, Alicia; Motrán, Claudia Cristina; Cervi, Laura (Frontiers in Immunology, 2019)
The production of IL-1-family cytokines such as IL-1β and IL-18 is finely regulated by inflammasome activation after the recognition of pathogens associated molecular pattern (PAMPs) and danger associated molecular patterns (DAMPs). However, little is known about the helminth-derived molecules capable of activating the inflammasome. In the case of the helminth trematode Fasciola hepatica, the secretion of different cathepsin L cysteine peptidases (FhCL) is crucial for the parasite survival. Among these enzymes, cathepsin L3 (FhCL3) is expressed mainly in the juvenile or invasive stage. The ability of FhCL3 to digest collagen has demonstrated to be critical for intestinal tissue invasion during juvenile larvae migration. However, there is no information about the interaction of FhCL3 with the immune system. It has been shown here that FhCL3 induces a non-canonical inflammasome activation in dendritic cells (DCs), leading to IL-1β and IL-18 production without a previous microbial priming. Interestingly, this activation was depending on the cysteine protease activity of FhCL3 and the NLRP3 receptor, but independent of caspase activation. We also show that FhCL3 is internalized by DCs, promoting pro-IL-1β cleaveage to its mature and biologically active form IL-1β, which is released to the extracellular environment. The FhCL3-induced NLRP3 inflammasome activation conditions DCs to promote a singular adaptive immune response, characterized by increased production of IFN- and IL-13. These data reveal an unexpected ability of FhCL3, a helminth-derived molecule, to activate the NLRP3 inflammasome, which is independent of the classical mechanism involving caspase activation.